THE ROLE OF THE GOVERNMENT IN THE LEGAL PROTECTION OF WORKERS PERFORMED BY TERMINATION OF EMPLOYMENT DURING THE COVID-19 PANDEMIC - Mahmuda Pancawisma Febriharini (Universitas 17 Agustus 1945 Semarang, 2022)
Covid-19 has shaken the Indonesian economy, and of course, the most significant impact felt due to this pandemic in industrial relations, both macro and micro. Many companies are threatened with the continuity of their production, which ultimately impacts the survival of workers in Indonesia. This condition emphasizes that the government needs to intervene in alleviating this problem. Based on this, this study aims to determine the government’s role in providing legal protection to workers who have been laid off due to the COVID-19 pandemic. The results in the field show that many workers have been laid off or laid off with wages that are not paid in full. To support the welfare and continuity of work for workers and to support workers who have been laid off or laid off due to Covid-19, the Government has issued various incentives for employers and workers, namely in the form of cash assistance in the form of Wage Subsidy Assistance (BSU) and issuing pre-employee cards aimed at providing training, namely providing skills that can be used for industrial and entrepreneurial needs.